"Ooh, It Was All So Awful". (October 2020) - Chapman, H.R.
This narrative illustrates how patient post-operative pain experiences can be influenced by worry, catastrophizing, previous learning experiences, and expectations about what will happen and how they will cope. It also demonstrates that a sympathetic dentist can help shape these expectations to the benefit of patients.